Faktor Utama Pengesahan Putusan MK Nomor 90/PUU-XXI/2023 Tentang Syarat Minimal Usia Capres dan Cawapres - Faisal, Bagus Imam; Ernawati; Mawardi, Imam; Yuniarti, Diah Retna; M. Sahid; Suldifa Jaya, R. Radika Suldifa Jaya (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2024)
This study aims to analyze the factors that are the main reasons behind the ratification of the Constitutional Court Decision (MK) Number 90/PUU-XXI/2023 regarding the minimum age requirements for presidential candidates and vice presidential candidates in Indonesia. This study involves the case study method in analyzing the decisions of the Constitutional Court (MK) and the judges' considerations in the decision-making process. This study identifies key factors that influence the ratification of the decision through an analysis of the Constitutional Court ruling. The first factor found was the need to give opportunities to young leaders who have potential and passion in leading the country. By lowering the minimum age limit, the Constitutional Court wants to ensure that the younger generation can actively participate in politics. The results of this study provide a detailed picture of the main factors affecting the ratification of the Constitutional Court decision Number 90/PUU-XXI/2023. As an implication, there are changes in regulations that regulate the minimum age requirements for presidential and vice-presidential candidates in Indonesia. This research can be useful for the government and relevant stakeholders to understand the thoughts and considerations behind this Constitutional Court ruling and take appropriate steps in the current political and social context.